Konsep Reksa Dana Syariah Menurut Fatwa DSN MUI - Idris, Nurul Muminati (Tijarah: Jurnal Ekonomi Syariah, 2023)
ABSTRACT            The increasing Development of muamalat in islamic investment, especially mutual funds sharia prove that islamic mutual funds are an alternative in improving the economy as well as being an economic system that is feasible, because of islamic mutual funds is deemed quite easy and does not require a large capital to be able to be a part of the islamic capital market or Islamic Financial Institutions, the need for an understanding of sharia mutual funds is the most basic thing to know before becoming the perpetrators of investors. DSN MUI as an institution that plays an important role in the issuing of a fatwa especially islamic economics has a role to determine whether or not a treatment is performed in terms of Islamic law.To maintain an Islamic Financial Institutions (LKS) remain on the line according to Islamic law then under the auspices of the DSN was established Sharia Supervisory Board (DPS) in order to carry out the functions of supervision of LKS in order not to violate the rules that have been set, as an external agency of LKS then DPS has a big responsibility as it has been regulated by laws and regulations of the DSN. ABSTRACT            The increasing Development of muamalat in islamic investment, especially mutual funds sharia prove that islamic mutual funds are an alternative in improving the economy as well as being an economic system that is feasible, because of islamic mutual funds is deemed quite easy and does not require a large capital to be able to be a part of the islamic capital market or Islamic Financial Institutions, the need for an understanding of sharia mutual funds is the most basic thing to know before becoming the perpetrators of investors. DSN MUI as an institution that plays an important role in the issuing of a fatwa especially islamic economics has a role to determine whether or not a treatment is performed in terms of Islamic law.To maintain an Islamic Financial Institutions (LKS) remain on the line according to Islamic law then under the auspices of the DSN was established Sharia Supervisory Board (DPS) in order to carry out the functions of supervision of LKS in order not to violate the rules that have been set, as an external agency of LKS then DPS has a big responsibility as it has been regulated by laws and regulations of the DSN.